Growth of Bacteria Isolat Consortium From Benakat on High Salainity Crude Oil Media - Astri Nugroho; Edison Effendi; Fiona Annisa (Jurnal ILMU DASAR, 2007)
The production and cunsumption of oil and petroleum product are increasing worldwide and threat of oil pollution is increasing accordingly. About 10 million tons of oil and petroleum products are used worldwide each day, it will occur 5% of all oil pollution entering the sea. For that reason, needs a treatment to handle and remediate aquatic ecosystem like former. Bioremediation is a process to detocsify dan degrade crude oil. Expected from this process, land and aquatic environment where were polluted by petroleum can be natural. Treatments are divided into three stages, which are (1) isolation of dominant microorganism that degraded petroleum hydrocarbon in 15% salinity and TPH 10%, (2) Identification of bacteria with biochemistry tes and Analytical Profile Index 20 NE test (3)Biodegradation ability test in 15%, 10% salinity and 30‰ (seawater salinity) and TPH (Total Petroleum Hidrocarbon) 1%, 2.5 %, 5 %, and 10 %. The microorganisms that were identified from the isolation crude oil from Benakat are Pseudomonas aeruginosa, Aeromonas hydrophila and Agrobacterium radiobacter. Total sel microorganisms/ml in exponential phase are P. aeruginosa: 2.42E/ml, A. hydrophila: 2.99E+14 /ml, A. radiobacter: 2.42E+14/ml, and mixed culture microorganism: 4.65E/ml. The average percentage sequence degradation from the optimum  growth are mixed culture = 92%, P. Aeruginosa = 90%, A. hydrophila = 88%, and A. radiobacter = 79%. The percentage sequence degradation of mixed culture in 15% salinity and 1%, 2,5%, 5%, 10% TPH concentration are 90%, 84%, 97%, 94%. Otherwise, 30‰ salinity and 1%, 5%, 10% TPH concentration, the percentage of biodegradation are 98%, 96%, 84%.